Urgensi Penggunaan Surat Keterangan Waris dalam Peralihan Hak sebagai Upaya Perlindungan dan Kepastian Hukum Ahli Waris - Anita, Avisena Aulia; Widodo, Muhammad Fajar Sidiq (MAHAKIM Journal of Islamic Family Law, 2023)
Transfer of rights occurs due to inheritance, which requires a Certificate of Inheritance as a requirement in processing the transfer of rights, especially those transferred due to Inheritance. This is stipulated as a condition for inheritance because the Inheritance Certificate is proof of the condition of the person who died (heir), the inheritance (boedel), and who the heirs are left behind. Not only that, this is also an effort to provide legal protection and certainty for heirs. The research method uses normative juridical, as well as statutory and conceptual approaches. Using descriptive analysis which aims to describe various problem formulations and provide solutions related to the problem formulations above. From the research, it was found that the issuance of a Certificate of Inheritance by an agency is considered important because it is a tool to facilitate the management of the transfer of rights that occurs due to inheritance, especially for heirs as users of the Certificate of Inheritance and one thing is certain wherever the Certificate of Inheritance is made and issued either through a Notary, Inheritance Hall or sub-district will have permanent, binding legal force and be legally valid.